Kekuatan Karakter pada Remaja Kristen dalam Pergaulan di Era Milenial: Kajian Pendidikan Agama Kristen yang Menghidupkan - Penta Astari; Lourine S. Joseph (Jurnal Shanan, 2023)
Millennials are the generation that lives by advances in technology that can affect their character. Instant teenage associations, promiscuity, smoking, drugs are things that appear in the lives of teenagers today. Along with that, a teenager's spirituality is closely related to the religious education he receives, whether at home, at church or at school. This study aims to find out the extent to which spirituality and Christian Religious Education that animates gives strength to the character of adolescents in the midst of their associations. This research uses the literature study method to find that spirituality and animate Christian Religious Education can give strength to the character of Christian adolescents in their associations, so that they do not lose their identity. The results of this study show that animate religious education provides a strong growth in the spirituality of adolescents in the face of their associations. Christian education can help a teenager to experience spiritual growth, through lifestyle or pilots from parents, teachers or religious leaders. The growing spiritulity followed by the enlivening Christian Religious Education gives a force that helps millennials to be able to stay strong and have good character in the face of the adverse effects of their association.